Indicators of high-quality general practice to achieve Quality Equity and Systems Transformation in Primary Health Care (QUEST-PHC) in Australia: a Delphi consensus study - Phyllis Lau; Samantha Ryan; Baneen Alrubayi; Lucy Bannister; Dylan Pakkiam; Penelope Abbott; Kathy Tannous; Steven Trankle; Kath Peters; Andrew Page; Natalie Cochrane; Tim Usherwood; et al. (PLoS ONE, 2025)
Objectives This study aimed to achieve wider consensus on the relevance and feasibility of the Quality Equity and Systems Transformation in Primary Health Care (QUEST-PHC) indicators and measures developed for Australian general practice. Methods Partnering with eight Primary Health Networks (PHNs) across four states, we conducted a Delphi consensus study consisting of three rounds of online survey with general practice experts including general practitioners, practice nurses and PHN staff members. Participants rated each measure for relevance and feasibility, and provided input into the implementation of a quality indicator tool. Each measure required ≥70% agreement in both relevance and feasibility to achieve consensus. Aggregated ratings were statistically analysed for response rates, means, standard deviations, ranges, and level of agreement. Sub-group analyses were conducted to compare the aggregated ratings between practice and PHN staff, and between clinicians and non-clinicians in the practice staff. Qualitative responses were analysed thematically using an inductive approach. Results Ninety-four participants participated in Round 1 survey; 61 completed all three rounds. All measures reached the consensus threshold for both relevance and feasibility; 19 were slightly less feasible when compared with other measures. Although in general the participants scored similarly and their agreements were statistically significant, subgroup analyses showed that PHN staff scored feasibility of some measures slightly lower than practice staff (e.g., patients screened for adverse childhood experiences), and clinicians also scored the feasibility of some measures slightly lower than non-clinicians (e.g., patient perceptions of preventative health discussion on unsafe sexual practices). Conclusions The QUEST PHC suite of indicators and measures have reached consensus in this Delphi study. Whilst the feasibility of some measures still needs considerations, the QUEST PHC suite provides a framework for defining and measuring high-quality general practice to enable reporting to inform quality improvement and alternative funding models for Australian general practice.